UJI DAYA TERIMA PADA JELLY DRINK KENIKIR (Cosmos caudatus Kunth.) - Lina Muflihatul Hamidah; Wiwik Afridah; Endah Budi Permana Putri (UNUSA Press, 2018)
Kenikir (Cosmos caudatus Kunt.) has high antioxidants level. Kenikir jelly drink is selected asa fungsional beverage and with natural antioxidants. This research aims determine to the testreceived power of kenikir jelly drink and to know the antioxidant activity and nutritional content ofpanelist’s favorite kenikir jelly drink. The research design is experimental with completed randomizenested one factor namely kenikir. The research population is kenikir jelly drink with sample of kenikirconcentration is 0% (control) and 5%,10%, 15%. The research instrument consists of 30 trainedpanelists and closed questionnaires. The analysis used is descriptive statistics, One Way Anove, thencontinued by Duncan Multiple Range Test, α = 0,05. The result of this research shows that 5% kenikirjelly drink has high received power (69,17%) by panelist. Based on Anova test, the p-value is 0,00which means that there is a difference of each treatment based on organoleptic test of color, taste,odor and texture parameters. Furthermore, the panelists favored sample were analyzed for theantioxidant and nutritional content. The result of this research shows that kenikir jelly drink 5% hashigh acceptance level with antioxidant activity of 86,61%, 83,13% of water content 0,20% of ash,16,77% of carbohydrate, 0,53% of crude fiber and 67,08 Kcal.of energy. The suggestion of thisresearch is the analysis of physical properties need to be held to know the food endurance of kenikirjelly drink.